Description and Key to the Fifth-Instars of Some Cicadas (Hemiptera: Cicadidae) Associated with Coffee Plants in Brazil - Maccagnan, D. H. B.; Martinelli, N. M. [UNESP] (Entomological Soc Brasil, 2011)
Fifth-instars of the cicada species Dorisiana drewseni (Stal), Dorisiana viridis (Olivier), Fidicina mannifera (Fabricius), Fidicinoides pronoe (Walker) and Carineta fasciculata (Germar) are described and illustrated. Moreover, a key to the nymphs of these species along with Quesada gigas (Olivier) is also provided.
Keywords: Cicadoidea; identification; immature; nymph; underground pest